The Educational Practice and Thought of the Second Polish Republic on the 90th Anniversary of Regaining Independence - Jamrożek, Wiesław (Biuletyn Historii Wychowania, 2018)
The situation of the Republic of Poland, which was revived in 1918, in the educational field was dramatically difficult. As a consequence of partitions, the Second Republic of Poland inherited a relatively high rate of analphabetism (over 6.5 million analphabets, which constituted approximately 33% of the entire population of the country older than 10 years). As a result of individual differences in the economic, political, social and legals systems of the states occupying Poland, the educational system on the Polish territories at the threshold of independence was largely different with regard to the number of schools, the organization, program and didactic assumptions. The reborn Polish state was confronted with an important task of unifying the system and the level of education. It must be emphasised that this task was actually accomplished. In this the Sejm on March 11, 1932 (the act conclusively dissolved the remains of the educational legislation of the states which partitioned Poland). In the interwar Poland, not only the school system but also the so-called extraschool education developed. The period of the Second Republic of Poland was also the time of explosion of pedagogic thought. The most important theoretical trends in the educational sciences emerged at that time, primarily: “psychological pedagogy and the related great movement of New Education (progressive education)”, “sociological pedagogics (social pedagogy)”, “cultural pedagogy (humanistic, personalistic pedagogy)”. A special object of reflection on the education in the Second Republic of Poland and of controversy in the pedagogics of the twenty years between the First and the Second World War in Poland was the question of educational aims. In the period until 1926 the dominant trend influencing the educational practice to the largest extent was the so-called patriotic education, whereas in the subsequent years citizenship education prevailed.